Prostate cancer in patients with suspected benign prostate hypertrophy in Juba, South Sudan: A retrospective study - Malong Aguer; Kenneth Sube; Garang Nyuol; Joseph Lako; Isaac Rial; Justin Tongun (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
Introduction: Prostate cancer carries a high morbidity and mortality especially when not diagnosed early. Patients in resource limited countries tend to be diagnosed late and hence delayed surgery for benign prostate hypertrophy (BPH). Method: This was a retrospective study, from 1st January 2019 to 31st December 2020, on patients who underwent prostatectomy. Demographic and clinical data were extracted from their medical records. Results: This study involved 101 patients who had had simple open prostatectomy. Ages ranged from 49 to 98 years, mean 68 +/- 8.98 years. The largest group (37.6%) was aged 71- 80 years, p=0.001. Two thirds (66%), presented with urinary retention, p=0.03. Histopathological examination showed that 49.5% had BPH. Prostate cancer was found in 28.8%, p=0.082. Almost half (49.5%) were diagnosed histopathologically as having BPH. Prostate cancer made up 28.8% with most patients in the age range 61-80 years, p= 0.456. Conclusion: The prevalence of prostate cancer remains high among patients undergoing prostatectomy for suspected BPH. A national awareness campaign coupled with targeted screening of patients above 40 years could increase early detection of prostate cancer and reduce morbidity and mortality.